X-Ray Crystalline Undulator Radiation in Water Window - Gevorgyan, H.
The problem of radiation produced by the bunch of relativistic positrons, channeled into the crystalline undulator, is considered, taking into account the polarization of a crystal medium. If a bunch energy is above the threshold energy, then the radiation is generated in the limited frequency range, due to the medium polarization. Both soft and hard boundary photons are emitted at a zero angle. When the ratio of the bunch energy to the threshold energy approaches unity from above, the peak of the bunch radiation spectrum is near the resonant frequency and can fall into the soft X-ray frequency range due a certain choice of the parameters of the crystalline undulator. In that case, it is necessary to use a low energy relativistic bunch. Method is effective because a fairly dense beam of soft X-ray photons is generated. It is shown the possibility of obtaining monochromatic, intense, directed photon beams in the water window region, important for medical and biological applications.
Keywords: Physics